DIFFERENCES IN THE WORK ETHIC OF TEACHERS WHO TEACH IN STATE SCHOOLS AND TEACHERS IN PRIVATE SCHOOLS AT SMA N 2 LENGAYANG AND SMK TECHNOLOGY LENGAYANG - Widia Suci Rahmadani; Kurniawan, Rizal (In Trend : International Journal of Trends in Global Psychological Science and Education, 2024)
This study aims to see how the work ethic of teachers who teach in state schools differs from teachers in private schools at SMA N 2 Lengayang and SMK Technology Lengayang. This study uses quantitative methods with a comparative quantitative design. The population in this study is teachers in state schools and teachers in private schools. The sampling technique in this study used a purposive sampling technique. This study has a sample of 60 teachers with details of 30 samples coming from SMA N 2 Lengayang and 30 samples from SMK Technology Lengayang. The instrument used in this study is the work ethic scale developed by Ngalia (2011) with a total of 27 items. This instrument is based on aspects of the work ethic from Cherrington (1980) which has 3 aspects including: work as a moral obligation, high work discipline, and pride in the results of work. Analysis result using independent sample t-test. The results of the data analysis test show that Ho is rejected and Ha is accepted with a significance value (2-tailed) of 0,048 < 0,05 which means that there is a difference in the work ethic of teachers who teach in state schools and teachers in private schools, where teachers in private schools have a higher work ethic.